2022
DOI: 10.1186/s13041-022-00983-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteins secreted by brain arteriolar smooth muscle cells are instructive for neural development

Abstract: Intercellular communication between vascular and nerve cells mediated by diffusible proteins has recently emerged as a critical intrinsic program for neural development. However, whether the vascular smooth muscle cell (VSMC) secretome regulates the connectivity of neural circuits remains unknown. Here, we show that conditioned medium from brain VSMC cultures enhances multiple neuronal functions, such as neuritogenesis, neuronal maturation, and survival, thereby improving circuit connectivity. However, protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Sorted cells were cultured in SMCM for further assay. The purity of cells sorted by the same method had been verified in the published paper (22).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Sorted cells were cultured in SMCM for further assay. The purity of cells sorted by the same method had been verified in the published paper (22).…”
mentioning
confidence: 85%
“…The electro-motor-driven brush stimulated the whisker longitudinally for 1 minute at a frequency of 12Hz. The principle of laser speckle contrast imaging has been described in the previous paper (21), and the operation referred to in the published paper ( 34, 58, 59 ). Laser Speckle Image System (RWD, RFSLI ZW/RFSLI III, CHN) was used to monitor the CBF change in the ROI of the opposite barrel cortex of mice.…”
Section: Methodsmentioning
confidence: 99%
“…It is well documented that development of the nervous system is highly dependent on appropriate signaling from adjacent non-neural tissues. Vascular smooth muscle cells in the brain, for example, secrete factors such as thrombospondin, a known synaptogenic factor, to promote neurite formation in mouse hippocampal neuronal cultures 7 . Proper expression of neurotrophic factors in the skin is also crucial for guiding peripheral sensory innervation, as demonstrated by studies showing that overexpression of neurotrophin-4 in the epidermal basal cells of mice leads to abnormally increased innervation of the dermal footpad [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary exploratory work indicated that, through an in vitro cell culture research system, the "secreted protein mixture" from human-derived blood vessel smooth muscle cells (HBvSMCs) and primary mouse meningeal aSMCs has a nutritive effect on mouse hippocampal and cortical neurons. This is manifested by effectively promoting the developmental processes of neuronal dendrites and increasing neuronal survival rates [17].…”
mentioning
confidence: 99%